Humphry Davy e a química agrícola: contribuições do conhecimento químico à prática agrícola na Inglaterra do início do século XIX - Costa, Alexandre Alves de Araujo (2010)
The agriculture, activity of primal importance for the human being, it is indeed a route of access for the application of the chemical knowledge towards its practice. Besides that, a sort of theoric concern that also configurated itself as one of the outlines on which was delineated the agricultural practices at the end of XVIII century and beginning of the XIX century, aiming the thecnincal development. Humphry Davy, who during his his career developed several studies with latent practical concerns, starts in 1802 one cycle of lectures about agricultural chemistry, supported by the Board of Agriculture, which extended until 1812, culminating with the publication of the book Elements of Agriculture in 1813. Davy, is usually known by his works with eletriciy and the posterior identification of several chemical elements. In his researchs, showed great interest towards nature and the composition of the matter, what was not different on agricultural researchs. Under the light of current historiography of science, this work intends to analyze how Humphry Davy used to explain the phenomena linked to vegetation, besides of the relevance of his books to agricultural practices